Pandemi Covid-19 dan Dampaknya Terhadap Klaim Asuransi di Indonesia: Studi Kasus BPJS Ketenagakerjaan: The Covid-19 and Its Impact On Insurance Claims in Indonesia: A Case Study of BPJS Ketenagakerjaan - Afrianto, Andri; Irawan, Tony; Asmara, Alla (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The COVID-19 virus has become a worldwide pandemic, and studies of its impact on insurance are needed. This paper aims to look at the impact of the COVID-19 pandemic on insurance by using the number of claim cases from BPJS Ketenagakerjaan in Indonesia, which covers 34 provinces. This study uses a time series spanning 2018-2021 and cross-sectional data from 11 regional offices of BPJS Ketenagakerjaan. The analytical method used in this research is static panel method. The dependent variable in this study is the number of claims cases (Claim) while the independent variables used are Covid19, per capita GRDP, and per capita -savings. Empirical findings suggest that COVID-19 cases are associated with additional insurance claims. Compared to before the pandemic, COVID-19 caused an average increase in claim cases by 0.2587845 per cent. Although the BPJS Ketenagakerjaan Program claims cases tend to increase every year, at the beginning of the pandemic, old-age security (JHT) and pension security (JP) programs were the most affected. Then in 2021, the death security (JKM), employment injury security (JKK), and pension security (JP) programs experienced the most significant increase in claim cases. Based on the results of the study, BPJS Ketenagakerjaan must prepare liquid funds to overcome the high number of claim cases during a pandemic such as the Covid-19 pandemic in the future. In addition, restrictions on community activities implemented by the government cause business processes to be developed digitally so that participants can carry out the claim process. Keywords: BPJS Ketenagakerjaan, COVID-19, Indonesia, insurance, insurance claim